Local support for conservation is associated with perceptions of good governance, social impacts, and ecological effectiveness. Issue 4 (12th March 2019) - Bennett, Nathan J.; Di Franco, Antonio; Calò, Antonio; Nethery, Elizabeth; Niccolini, Federico; Milazzo, Marco; Guidetti, Paolo
Abstract: Local support is important for the longevity of conservation initiatives. The literature suggests that perceptions of ecological effectiveness, social impacts, and good governance will influence levels of local support for conservation. This paper examines these relationships using data from a survey of small‐scale fishermen in 11 marine protected areas from six countries in the Mediterranean Sea. The survey queried small‐scale fishermen regarding perceptions and support for conservation. We constructed composite scores for three categories of perceptions—ecological effectiveness, social impacts, and good governance—and tested the relationship with levels of support using ordinal regression models. While all three factors were positively correlated with support for conservation, perceptions of good governance and social impacts were stronger predictors of increasing support. These findings suggest that employing good governance processes and managing social impacts may be more important than ecological effectiveness for maintaining local support for conservation.